A regulatory axis for tonotopic MYO7A expression in cochlear hair cells - Sihan Li; Sujin Jun; Ye-Ri Kim; Ayathi Gogineni; Franklin Lee; Chul Hoon Kim; Un-Kyung Kim; Anthony W. Peng; Jung-Bum Shin (Proceedings of the National Academy of Sciences, 2026)
Myo7a , a gene mutated in Usher syndrome and nonsyndromic deafness, encodes an unconventional myosin essential for hair cell function. Our previous work revealed that cochlear hair cells express distinct Myo7a isoforms with unique spatial and cell type–specific patterns. The canonical isoform ( Myo7a-C ) and an additional isoform ( Myo7a-N ) are co-expressed in outer hair cells (OHCs) but exhibit opposing tonotopic gradients, while inner hair cells primarily express Myo7a-C . These isoforms arise from distinct transcriptional start sites, indicating separate regulatory inputs. Here, we identify an intronic cis- regulatory element, EnhancerA , essential for tonotopically graded Myo7a expression. EnhancerA deletion reduces MYO7A protein levels in a tonotopically varied manner, disrupts hair bundle morphogenesis, alters OHC mechanotransduction, and leads to hair cell degeneration and hearing loss. We further identify SIX2, a tonotopically expressed transcription factor that may interact with EnhancerA to regulate Myo7a-N in OHCs. These findings define a cis–trans regulatory axis critical for isoform-specific Myo7a expression and cochlear function.